A CORRELATION BETWEEN VOCABULARY AND SENTENCE STRUCTURE MASTERY TOWARDS READING COMPREHENTION OF PRIVATE UNIVERSITY STUDENTS IN WEST JAKARTA - Julyanta br sitepu (STIBA IEC JAKARTA, 2018)
The research is conducted to prove a correlation between vocabulary and sentence structure mastery towards reading comprehension of private university students. The methodology used in this research is a survey of regression and correlation analysis which relates between the data and correlation between vocabulary and sentence structure mastery towards students’ reading comprehension. The research uses three variables, two independent variables (vocabulary and sentence structure mastery), and one dependent variable (reading comprehension). The data is collected by using vocabulary, sentence structure and reading tests. The research found that: 1) There is a significant correlation between vocabulary and sentence structure mastery towards students’ reading comprehension, proven by the result of Sig. 0.000 < 0.05 and F-test = 15.011. 2). There is a significant correlation between vocabulary mastery towards students’ reading comprehension, proven by the result of Sig. 0.008 < 0.05 and t-test = 2.744. 3). There is a significant correlation between sentence structure mastery towards students’ reading comprehension, proven by the result of Sig. 0.011 < 0.05 and t-test = 2.617.